Islamic Law and Fraud Eradication Strategy in Islamic Financial Institutions - Pradesyah, Riyan; Nawir Yuslem; Chuzaimah Batubara (Faculty of Law, Universitas Pekalongan, 2024)
This study examines the law and strategy to eradicate fraud in Islamic financial institutions, which are important institutions in the sharia-based economy. Fraud, which includes various fraudulent acts such as manipulation of financial statements and abuse of authority, can damage the reputation and sustainability of financial institutions. Therefore, a thorough understanding of the laws governing Islamic financial institutions, including the Sharia Banking Law and regulations from the Financial Services Authority (OJK), is essential in efforts to prevent and counter fraud. The fraud eradication strategy proposed in this study involves several approaches. First, the implementation of a comprehensive internal control system, including periodic internal and external audits, to ensure transparency and accountability. Second, increasing awareness and ethical training for employees, so that they are better able to recognize and prevent fraud. Third, the use of information technology, such as early detection systems and data analysis, which can identify suspicious patterns in financial transactions. This research emphasizes the importance of collaboration between Islamic financial institutions, regulators, and the public to build a safe and transparent ecosystem. Thus, efforts to eradicate fraud not only protect institutional assets, but also strengthen public trust in the Islamic financial system. The results of this research are expected to provide insight for policy makers and practitioners in developing more effective strategies in eradicating fraud.